Nomenclatoral changes for some Pseudophyllinae (Orthoptera, Tettigoniidae) - Braun, Holger; Maehr, Michael D. (Zootaxa, 2008)
Recently Özdikmen (2007 & 2008) proposed substitute names for two generic names in the subfamily Pseudophyllinae which are junior homonyms: Colobotettix Beier 1960 (preoccupied by a leafhopper genus) was renamed Beierotettix and Alloschema Beier 1954 (preoccupied by a weevil) became Beieroschema. Similarly in accordance with article 60 of the International Code of Zoological Nomenclature (1999) we propose substitute names for two additional genus group names in the same subfamily, concerning also Neotropical taxa described by Beier.